DESIGNING MOTION GRAPHIC AS A CORPORATE CULTURE KALLA GROUP SOCIALIZATION - Muin, Suardi (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2021)
The purpose of this design is to create information media in the form of motion graphics that can introduce and explain the Kalla group's corporate culture. As well as increasing the productivity and loyalty of the workforce in the Kalla group company. Especially employees who are in Makassar. The data analysis method used is SWOT and qualitative analysis. The collection of data collected was obtained from direct field observations, interviews, documentation and questionnaires. Then proceed with the design process by determining the main concept. The main concept used is corporate concept design where the form, story and visuals are used not far from the vision and mission and GSM of the company. After giving the concept, then making visual concepts, storylines, storyboards, digitizing, animating, to the process of composing. The result of this design is in the form of motion graphics which is the main media. The reason is, this media is a media that suits the target audience and is also practical to be seen repeatedly. Supporting media in the form of flash cards to facilitate video storage and X-banners. And the promotional media used digital promotional media such as blast email, Instagram and also youtube. To facilitate the internal deployment of the company design.